Classifying drinking water contaminants for regulatory consideration (National Academy Press, 2001)
This is the third report by the Committee on Drinking Water Contaminants (jointly overseen by the National Research Council's [NRC's] Water Science and Technology Board and Board on Environmental Studies and Toxicology). The committee was formed early in 1998 at the request of EPA's Office of Ground Water and Drinking Water to provide advice regarding the setting of priorities among drinking water contaminants in order to identify those contaminants that pose the greatest threats to public health. The committee is comprised of 14 volunteer experts in water treatment engineering, toxicology, public health, epidemiology, water and analytical chemistry, risk assessment, risk communication, public water system operations, and microbiology. For this report, EPA asked the committee--which was partially reconstituted after the second report to include a new chair--to evaluate, expand, and revise as necessary the conceptual approach to the generation of future CCLs and any related conclusions and recommendations documented in the second report. In addition, EPA asked the committee to explore the feasibility of developing and using mechanisms for identifying emerging microbial pathogens (using what the committee now terms virulence-factor activity relationships, or VFARs) for research and regulatory activities--also as recommended in the second report. The contents, conclusions, and recommendations in this report are based on a review of relevant technical literature, information gathered at three committee meetings, and the expertise of committee members. As in its first two reports, the committee continues to emphasize the need for expert judgment throughout all CCL-related processes and for a conservative approach that errs on the side of public health protection.